Faktor-Faktor Yang Mempengaruhi Kepuasan Pelanggan Yuke Fresh Laundry Di Jakarta Pusat - Dhefitriana Kartika; Aang Syahdina; Hansel Aristo; Nur Rahmah Wati; Varent Dwi Ch (AKSIOMA : Jurnal Manajemen, 2024)
This research is expected to be useful for assessing the driving factors of customer satisfaction with the place, service quality, and price of Yuke Fresh Laundry in Central Jakarta. The population in this study are all customers of Yuke Fresh Laundry. The purposive sampling technique is a technique used in this study in selecting samples. 100 respondents is the number of samples used in this study. The data collected through the survey was analysed using SmartPLS version 4.0 with Structural Equation Modeling. The results showed that the location factor has the most significant influence on customer satisfaction with a T-statistic value of 2.182 and a P-value of 0.029. Price also has a significant effect, while service quality does not have a significant effect on customer satisfaction. In other words, the main focus of improving customer satisfaction is on location and pricing strategies.